Anaerobic Oxidation of Toluene, Phenol, and p-Cresol by the Dissimilatory Iron-Reducing Organism, GS-15 - Lovley, Derek R. (1990)
The dissimilatory Fe(III) reducer, GS-15, is the first microorganism known to couple the oxidation of aromatic compounds to the reduction of Fe(III) and the first example of a pure culture of any kind known to anaerobically oxidize an aromatic hydrocarbon, toluene. In this study, the metabolism of toluene, phenol, and p-cresol by GS-15 was investigated in more detail. GS-15 grew in an anaerobic medium with toluene as the sole electron donor and Fe(III) oxide as the electron acceptor. Growth coincided with Fe(III) reduction. [ring-(14)C]toluene was oxidized to (14)CO(2), and the stoichiometry of (14)CO(2) production and Fe(III) reduction indicated that GS-15 completely oxidized toluene to carbon dioxide with Fe(III) as the electron acceptor. Magnetite was the primary iron end product during toluene oxidation. Phenol and p-cresol were also completely oxidized to carbon dioxide with Fe(III) as the sole electron acceptor, and GS-15 could obtain energy to support growth by oxidizing either of these compounds as the sole electron donor. p-Hydroxybenzoate was a transitory extracellular intermediate of phenol and p-cresol metabolism but not of toluene metabolism. GS-15 oxidized potential aromatic intermediates in the oxidation of toluene (benzylalcohol and benzaldehyde) and p-cresol (p-hydroxybenzylalcohol and p-hydroxybenzaldehyde). The metabolism described here provides a model for how aromatic hydrocarbons and phenols may be oxidized with the reduction of Fe(III) in contaminated aquifers and petroleum-containing sediments.